Effect of magnetite on the catalytic oxidation of polycyclic aromatic hydrocarbons in fly ash from MSW incineration: A comparative study of one-step and two-step hydrothermal processes. (1st February 2022) - Shi, Dezhi; Lv, Mengying; Tong, Haihang; Liu, Jiayu; Cai, Huayi; Luo, Dan; Ma, Cailing; Xu, Xiaoyi; Wang, Bin
Abstract: Polycyclic aromatic hydrocarbons (PAHs), many of which are carcinogenic, teratogenic, and mutagenic, exist in fly ash (FA) produced from municipal solid waste incineration (MSWI). Hydrothermal treatment (HT) is an efficient approach to remove PAHs from MSWI FA. Here, magnetite (Fe3 O4 ) was used as the catalyst and hydrogen peroxide (H2 O2 ) as the oxidant for one-step and two-step catalytic hydrothermal methods. When the magnetite dosage increased to 15 wt%, the maximum degradation rates of PAHs were 84.36% and 92.51%, respectively; however, the toxicity equivalent quantity (TEQ) degradation rates of the PAHs both increased upon increasing the magnetite dose. At 20 wt% Fe3 O4, the maximum TEQ degradation rates of the PAHs were 93.29% and 97.76%, respectively. The reaction between OH and PAHs is non-selective, which means that LMW, MMW, and HMW PAHs were all degraded. The decrease in TEQ was mainly due to the degradation of HMW PAHs, i.e., those with five rings. Under the same Fe3 O4 dose, oxidant dose, and reaction time, the detoxification of PAHs by the two-step method was significantly better than that of the one-step method, possibly because the two-step method more effectively produced OH. The first step degraded more than 90% of PAHs, and the residual PAHs in the HT products of the first step limited the utilization of the oxidant during the second step. The minerals in the HT products implied that the two-step hydrothermal method not only produced more OH, which reacted with PAHs, but also generated metal-magnetite substitution, which affected its surface reactivity during heavy metal adsorption and catalysis. These results revealed that both magnetite and the two-step hydrothermal treatment degraded PAHs. 20 wt% magnetite was the optimal amount during the two-step hydrothermal catalytic oxidation of MSWI FA. Highlights: Fe3 O4 is good for degradation of PAHs in FA by hydrothermal catalytic oxidation. With same H2 O2 dose and reaction time, detoxification by novel two steps was better. HMW PAHs especially 5-ringed PAHs mainly contributed to reduction of TEQ of PAHs. Degradation of PAHs in 1st step accounts for more than 90% in two-step method. Mechanism can be related with OH produced and metal-magnetite substitution formation.